PREDIKSI PERMINTAAN MATA KULIAH SEMESTER ANTARA (PADAT) DENGAN MENGGUNAKAN ALGORITMA FOLD-GROWTH DAN FP-GROWTH - Parulian, L Taufik; Doharma, Rouly; Taufik, Ahmad (Infotech: Journal of Technology Information, 2023)
The intermediate semester is the lecture period which is held during the holidays between even and odd semesters which is one of the alternatives given to students. The main purpose of predicting the demand for intermediate semester courses is to be able to help students make improvements to less than optimal grades and to be able to shorten the lecture period. All forms of preparation, both schedules and lecturers' appointments made by the higher education institution are related to requests for courses to be followed by students. Frequent Pattern-Growth (FP-Growth) is an alternative algorithm that can be used to determine the most frequent data set (frequent item set) in a data set. The Fold-growth algorithm uses the SOTrieIT data structure to extract transaction patterns. The expected results in this study are to predict the courses that will be taken by students in the solid / intermediate semester so that the leadership can make good preparations.